Липет йылын зор эктэ: пиналъёслы кылбуръёс / Лидия Чернова - Чернова Лидия Дмитриевна (Удмуртия, 2012)
Экземпляры: ф. 1 (20130312) / Инвентарный номер: 99548 / Цена: 40.00 / Авт.знак: Ч-49 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)